FDG‐PET detects nonuniform muscle activity in the lower body during human gait. Issue 5 (19th May 2016) - Kindred, John H.; Ketelhut, Nathaniel B.; Benson, John‐Michael; Rudroff, Thorsten
ABSTRACT: Introduction : Nonuniform muscle activity has been partially explained by anatomically defined neuromuscular compartments. The purpose of this study was to investigate the uniformity of skeletal muscle activity during walking. Methods : Eight participants walked at a self‐selected speed, and muscle activity was quantified using [ 18 F]‐fluorodeoxyglucose positron emission tomography imaging. Seventeen muscles were divided into 10 equal length sections, and within muscle activity was compared. Results : Nonuniform activity was detected in 12 of 17 muscles (ƒ > 4.074; P < 0.046), which included both uni‐ and multi‐articular muscles. Greater proximal activity was detected in 6 muscles ( P < 0.049), and greater distal versus medial activity was found in the iliopsoas ( P < 0.042). Conclusions : Nonuniform muscle activity is likely related to recruitment of motor units located within separate neuromuscular compartments. These findings indicate that neuromuscular compartments are recruited selectively to allow for efficient energy transfer, and these patterns may be task‐dependent. Muscle Nerve 54 : 959–966, 2016